Proceedings of the 2012 iConference 2012
DOI: 10.1145/2132176.2132209
|View full text |Cite
|
Sign up to set email alerts
|

Historical ontology and infrastructure

Abstract: We explore the relationship between long-term scientific infrastructure and its changing objects of research. Specifically, we focus on the historical changes in HIV disease during the life of a longitudinal medical study investigating the disease for nearly thirty years. We ask, within the study of information infrastructure and research-based organizations, what are the things that inherently change, and how do such changes reverberate through the practice and organization of infrastructure? In applying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…However, research infrastructure is not only a sociotechnical system ready at hand, but also technoscientific, i.e., purposefully oriented to investigating an array of research objects (Ribes & Polk, 2012;Ribes, 2014). Over time, research infrastructure also faces changing objects of research, instruments, and methods of science.…”
Section: Technoscientific Changementioning
confidence: 99%
“…However, research infrastructure is not only a sociotechnical system ready at hand, but also technoscientific, i.e., purposefully oriented to investigating an array of research objects (Ribes & Polk, 2012;Ribes, 2014). Over time, research infrastructure also faces changing objects of research, instruments, and methods of science.…”
Section: Technoscientific Changementioning
confidence: 99%
“…Star also recommended focusing on one BO in any particular study, and—based on our review—we agree with this recommendation in most cases. Studying the sociotechnical infrastructure (Edwards, Bowker, Jackson, & Williams, ; Ribes et al, ) and sociomaterial assemblage (Suchman, ), however, means considering the roles of many different objects within a sociotechnical or sociomaterial system. Most studies will have a main BO of interest and focus—a system, artifact, document, classification, or other object—but there will be additional BOs of potential interest that should not be discarded from further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of van den Hoven's () acknowledgment that Rawls's focus on the basic structure equips us with powerful tools for thinking about ethics in the context of design—scholars have largely overlooked the importance of the argument from the basic structure. At the same time, scholars from the area of science and technology studies have shown how the sociotechnical practices enabled by various infrastructures organize and make useful resources necessary for the operation and upkeep of political, economic, and social practices (Bowker & Star, ; Bowker, Baker, Millerand, & Ribes, ; Ribes & Polk, )—practices that make up and sustain the very background conditions with which Rawls is concerned. These discussions may offer new insight into how to best understand the relationships between institutions, individuals, and practices that make up Rawls's basic structure.…”
Section: Discussion and Possible Paths Forwardmentioning
confidence: 99%